Analysis of Cultural Aspects in the Movie “Eat, Pray, Love” - Yanti, Firda; Nur, Sahril; Fitriyani (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2024)
Humans use language as a tool to communicate with each other. Language can create a meaning that someone wants so as to prevent conflict in society. Language is also not only used for communication about everyday life but is also very important in intercultural communication with others, with the aim of spreading existing cultures so that they are preserved. Talking about culture and language certainly includes types of culture, where culture contains aspects that can be found in various literary works, one of which is movies. Movies are a form of literary work that can explore various studies, including cultural aspects. This thesis focuses on the cultural aspects of the activities of the characters in the movie. In analyzing cultural aspects, of course, it cannot be separated from the characters who play an important role in the movie or are usually called the main characters and supporting characters. In this study, the we used the theory of Cortazzi and Jin (1999). To analyze the data, the we used the anthropolinguistic approach and descriptive qualitative methods. The results of the study were obtained from the movie transcript, which was then interpreted and explained in detail. Based on the results of the study, there are three types of culture spoken by the main character. The three types of culture are source culture, target culture, and international culture.